Clinicopathological Profile of Oral Squamous Cell Carcinoma in Eastern India - Surendra Nath Senapati (JCDR Research and Publications Private Limited, 2021)
Introduction: Head and Neck cancer is most common cancer in developing countries like India. Oral Squamous Cell Carcinoma (OSCC) is the most common site of head and neck malignancy. Various histopathological factors prognosticates the therapeutic outcome. Clinicopathological characteristics of OSCC in Asian countries somehow differ from Western countries. Aim: To report the different clinicopathological characteristics of OSCC due to paucity of the literature even though it is one of the most common malignancy in India. Materials and Methods: In this retrospective observational study, the medical records of 1753 patients of OSCC who satisfied the eligibility criteria and were treated at a tertiary cancer centre at Cuttack, Odisha, India, from January 2009 to December 2019. Clinicopathological profile of the included subjects were noted. The data was analysed in the month of March 2021 using descriptive statistics such as mean, median, maximum, minimum value and percentage using International Business Machine (IBM) Statistical Package for the Social Sciences (SPSS) version 23.0. Results: Total of 1753 patients were analysed with the mean age of 50.55±12.56 years, however, majority 492 (28.1%) were in the age of 40-49 years. Male predominance was observed in 1379 (78.7%) patients. Buccal mucosa was the most common primary site in 731 (41.7%) patients, (41.7%) followed by the tongue in 359 (20.5%) patients. Left side lesion was seen in 1008 (57.5%) patients while 734 (41.9%) patients had lesion at right side. Morphologically, ulceroinfiltrative lesion was the most common presentation constituting in 897 (51.2%) patients. Maximum tumour size was 2.91±1.25 cm. Maximum number of patients i.e., 1529 (87.2%) had grade I disease. Mean Depth of Invasion (DOI) was 8.67±4.50 mm. Lymphovascular Space Invasion (LVI) was positive in 123 (7%) patients and Perineural Invasion (PNI) was observed in 565 (32.2%) patients. Resected margin was positive in 203 (11.6%) patients. Cervical lymph node involvement was found in 691 (39.4%) patients and 28 (1.6%) had extracapsular extension. In the present study, most of the patients presented in advanced stage of the disease i.e., stage III 380 (21.7%) and stage IV 506 (28.9%). Conclusion: The present study highlights that majority of OSCC presents in younger age groups, as left side buccal mucosal lesion with advanced stages of disease. This scenario is due to poor lifestyle pattern which can be prevented by avoidance of tobacco consumption, active screening, public awareness and early diagnosis.